2018
DOI: 10.4317/medoral.22474
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal therapy for patients before and after radiotherapy: A review of the literature and topics of interest for clinicians

Abstract: BackgroundTo review and discuss important topics regarding periodontal treatment pre- and post-radiotherapy for head and neck cancer in human patients; to discuss the references for adequate techniques, the appropriate moment for tooth extractions and periodontal management; and to discuss the prevention of osteoradionecrosis.Material and MethodsThirty-nine studies including original studies, randomized clinical trials (RCTs) and reviews were searched in online databases MEDLINE (PubMed) and the Cochrane libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 38 publications
1
40
0
7
Order By: Relevance
“…First, patients with oral cancer receive a higher dose of RT in their oral cavity than those with non‐oral HNC 6 . Accordingly, more oral complications occur, such as extensive caries, periodontal destruction, xerostomia, oral candida infection and trismus, 8,16 and may result in new teeth with a poor prognosis, jaw bone damage or new sources of infection, all of which can, in turn, increase the ORNJ risk 36 . Second, the aggressive surgical approach required by tumour resection of oral cavity cancer frequently involves the removal of arteries necessary to maintain mandibular blood flow, thus possibly increasing the ORNJ risk 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, patients with oral cancer receive a higher dose of RT in their oral cavity than those with non‐oral HNC 6 . Accordingly, more oral complications occur, such as extensive caries, periodontal destruction, xerostomia, oral candida infection and trismus, 8,16 and may result in new teeth with a poor prognosis, jaw bone damage or new sources of infection, all of which can, in turn, increase the ORNJ risk 36 . Second, the aggressive surgical approach required by tumour resection of oral cavity cancer frequently involves the removal of arteries necessary to maintain mandibular blood flow, thus possibly increasing the ORNJ risk 37 .…”
Section: Discussionmentioning
confidence: 99%
“…One vital aspect of this is the time interval between tooth extraction and the first day of RT, which must be sufficient to allow initial healing of the extraction wound and avoid iatrogenic ORNJ. Most studies have concluded that tooth extraction should be performed at least 7‐21 days before RT 8,12‐16 . However, the wound‐healing time should not be prolonged because this could compromise oncological treatment and prognosis 13,17‐20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During such treatment, it is common for changes in the oral cavity to occur: such changes include mucositis, ulceration, gingival bleeding [2],degeneration in oral keratinocytes [3] and altered collagen synthesis [4], as well as changes in connective tissue and the oral microbial environment [5]. Furthermore there is increased destruction of periodontal tissues [6,7] with progressive periodontal attachment loss [8], increased production of proinflammatory cytokines [9] and the remodelling ability of bone and soft tissue is compromised [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both acute and long‐term effects of radiation to the head and neck are associated with a decreased quality of life . There is general consensus that patients exposed to radiation to the head and neck need adequate follow‐up to prevent or reduce adverse effects and the need for communication between various caregivers is advocated . It is also important to motivate the patient for subsequent follow‐up, adequate oral hygiene and long‐term use of salivary stimulants/salivary substitutes and fluoride prophylaxis …”
Section: Introductionmentioning
confidence: 99%